Virtual social media communities and their effects on World Englishes - Almohawes Monera (Journal of Language and Cultural Education)
This paper investigates the impact of social media use and virtual communities on world Englishes. The term world Englishes refers to the different varieties of how English is communicated worldwide. Kachru (1985) described the language’s spread in terms of three concentric circles: the inner circle, the outer circle, and the expanding circle. The inner circle comprises traditional bases of English where it serves as speakers’ first language, such as in the United Kingdom, the United States, and Australia. The outer circle refers to countries where English is an official second language, such as India and Kenya. The expanding circle includes countries where English is spoken as a foreign language or lingua franca, such as countries in Europe and the Middle East, as well as Japan. By exploring the varieties of English on social media, in this paper, the researcher examined how social media and digital communication affect these circles of world Englishes and how users position and use English. The researcher qualitatively analysed 15 X Spaces (former Twitter) following Mesthrie and Bhatt’s (2008) method of analysing syntactic and morphological structures and then examining the pragmatics features and discourse. This included the following components: (a) the noun phrase (b) the verb phrase and (c) other function words. The results show that people are using new Englishes in virtual communities. There are many variations in language use in the structural features of the participants’ language morphology, phrasal syntax, and pragmatics. The participants invented and used new language structures and understood them among each other. Based on this finding, in future studies, researchers could examine new Englishes in other virtual communities and their effects on people’s identities and languages.